Olga Kirsch se posisie in die Afrikaanse literêre sisteem (1900-1978) / Olga Kirsch’s Position in the Afrikaans Literary System (1900-1978) - Senekal, Burgert (Werkwinkel, 2014)
Centrality and marginality are important concepts in polysystem theory, and also in network theory. This article examines Olga Kirsch’s position in the Afrikaans literary system by taking into account data spanning from 1900 to 1978. Overall centrality is discussed from the perspective of network theory and related to polysystem theory, and the concept is also applied to the literary system through the use of the Fruchterman and Reingold (1991) force-directed layout algorithm. It is indicated that Kirsch is positioned on the edge of the core or in the semicore, mainly because there are not so many people from the core who had paid attention to her works, but also because she, according to this data set, did not write on the works of others. It is also indicated which important critics, literary scholars and literary historians paid attention to her works, which contributes to her not being positioned on the periphery.